Forms of Hybridity in Travel Blogs - Anesa, Patrizia (HERMES - Journal of Language and Communication in Business, 2018)
The technological revolution has changed considerably not only the way people travel and but also how they narrate their experiences. In this respect, the analysis of travel blogs can offer insights into the discursive and communicative practices which characterize this hybrid genre. This study is based on the investigation of a corpus of highly visited travel blogs and aims to observe their hybridity from a multitude of perspectives. More specifically, hybridity is seen in terms of genre, (a)synchronicity, collaboration, modes of communication and level of multimodality, style, orientation, levels of subjectivity and pragmatic functions. From a lexical perspective, specific attention is devoted to evaluative adjectives. In particular, the use of adjectives belonging to conceptual classes such as ‘assessment’ or ‘deviance’ is a widespread tool to express the blogger’s subjectivity and may assume different communicative and pragmatic functions.